Tensile Properties And Water Absorption Of Mineral Fillers Filled Polylactic Acid Composites - Idris, Muhammad Yusran Azim (Universiti Sains Malaysia, 2022)
Addition of mineral fillers into the biodegradable polymer has been studied to identify the properties of composite materials. The study is aimed to identify the optimum loadings of different types of mineral fillers (talc, siltech G500, and Siltech G501) in polylactic acid (PLA). Due to the brittle properties of PLA, polyethylene glycol plasticizer (PEG) was blended with PLA. The effects of plasticizer were investigated using three different PEG loadings. Mineral fillers were characterized using particle size analyser (PSA) and scanning electron microscope to identify the particle size distribution, shape, and size of the particles. Mineral fillers filled PLA/PEG blends were mixed using twin-screw extruder. Injection moulding were used to fabricate the test sample according to the standard ASTM D638. Tensile properties such as tensile strength, elongation at break, and Young’s modulus were obtained for different composition of mineral filled PLA composites. Water absorption test was done to investigate the rate of water absorption in composite materials in comparison with PLA/PEG. Tensile properties indicated that PLA/PEG 15 % is the best formulation exhibits higher in elongation at break and impact strength. For mineral fillers filled PLA/PEG, the best fillers are 30 wt % of Talc and Siltech G500. Results showed that the tensile strength and elongation at break trend decreased with addition of fillers and Young’s modulus increased. Water absorption rate results showed that, PLA/PEG without any fillers having lower water absorption rate if compared with the mineral fillers filled in PLA/PEG. Thus, the best fillers in PLA/PEG composites is 30 wt % talc.